The inhabitants of Gacko at work in Dubrovnik (XIV–XV century) - Pekić, Radmilo B. (Collection of Papers of the Faculty of Philosophy in Priština, 2016)
The process of emigration from the area of ​​Hum and Trebinje area to medieval Dubrovnik as a phenomenon existed for centuries. The causes for this were differents in different periods, and it’s already well documented. However, from this broad process, this paper is limited to the population of Gacko only, which emigrated during the XIV and XV century in Dubrovnik to find a job and to learn a skill of a craft. On the basis of published and unpublished sources from Dubrovnik, the author establishes the conditions under which the medieval population from Gacko served and learned crafts in Dubrovnik.